Exogenous spermine alleviates the negative effects of combined salinity and paraquat in tomato plants by decreasing stress-induced oxidative damage - Pascual, Lidia S.; López-Climent, María F.; Segarra-Medina, Clara; Gómez-Cadenas, Aurelio; Zandalinas, Sara I. (Frontiers in Plant Science, 2023)
Plants are frequently exposed to different combinations of soil constraints including salinity and different herbicides. These abiotic conditions negatively affect photosynthesis, growth and plant development resulting in limitations in agriculture production. To respond to these conditions, plants accumulate different metabolites that restore cellular homeostasis and are key for stress acclimation processes. In this work, we analyzed the role of exogenous spermine (Spm), a polyamine involved in plant tolerance to abiotic stress, in tomato responses to the combination of salinity (S) and the herbicide paraquat (PQ). Our findings showed that application of Spm reduced leaf damage and enhanced survival, growth, photosystem II function and photosynthetic rate of tomato plants subjected to the combination of S and PQ. In addition, we revealed that exogenous Spm reduced H2O2 and malondialdehyde (MDA) accumulation in plants subjected to S+PQ, suggesting that the role of exogenous Spm in alleviating the negative effects of this stress combination could be attributed to a decrease in stress-induced oxidative damage in tomato plants. Taken together, our results identify a key role for Spm in improving plant tolerance to combined stress.